(untitled) (Research, Society and Development, 2020)
Objective: Evaluate, through a systematic literature review, the efficacy of manual therapy (MT) in the release of masticatory muscles in patients with temporomandibular disorders (TMD) compared to other forms of treatment. Methods: Electronic databases as SCOPUS, PUBMED and Web of Science were used to search for randomized controlled clinical trials. The selected trials were classified according to the Jadad scale. Results: The combined use of MT with education and self-care may be safer than performing as an isolated technique when considering a period longer than 1 year due to the maintenance of the effect. Conclusions: The included studies concluded that MT alone has significant effects on pain reduction at different follow-up periods. However, due to the diversity in number of sessions, duration of sessions and follow-up times, it becomes necessary to use standardized protocols.